Children’s exposure and Atlantic crossings: the passage of practices and people to the extreme south of Portuguese America (1750-1810) - da Silva, Jonathan Fachini (Esboços: histories in global contexts, 2021)
The exposure of children was a common phenomenon in the Catholic universe of the modern period. Widely practiced and tolerated in Iberian territory, the phenomenon took on new proportions with European expansions, starting in the 16th century, arriving along with the colonizer in the new territorial spaces. It is precisely in order to perceive the expansion of this practice that this article analyzes the Atlantic crossings of exposed people, who were rejected in Lisbon in their childhood, survived, grew up and travelled to Portuguese America, where they settled. With the support of Social History and a theoretical contribution inspired by Italian micro history, we realized how these trajectories can shed light on the theme of children’s exposure, the spread of this practice, on both sides of the Atlantic.